1999
DOI: 10.1074/jbc.274.49.35119
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and Biochemical Differences in the TCR·CD3 Complex of CD8+ Versus CD4+ Mature Lymphocytes Revealed in the Absence of CD3γ

Abstract: Mature CD4؉ and CD8 ؉ T lymphocytes are believed to build and express essentially identical surface ␣␤ T-cell receptor-CD3 (TCR⅐CD3) complexes. However, TCR⅐CD3 expression has been shown to be more impaired in CD8 ؉ cells than in CD4؉ cells when CD3␥ is absent in humans or mice. We have addressed this paradox by performing a detailed phenotypical and biochemical analysis of the TCR⅐CD3 complex in human CD3␥-deficient CD8؉ and CD4 ؉ T cells. The results indicated that the membrane TCR⅐CD3 complex of CD8 ؉ T lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…5 and 7, respectively), which were regulated by activation and differentiation for certain epitopes, likely due to lipid raft-dependent arrangements or glycosylation. These results confirm our previous biosynthetic and phenotypic studies in CD3␥-deficient T cells (6) and extend the observations to primary T lymphocytes from normal individuals. Biosynthetic studies showed that CD8 ϩ but not CD4 ϩ CD3␥-deficient T cells contained a small ␣␤ heterodimer composed of abnormally glycosylated TCR␤ and an abnormally small CD3-associated chain that was not recognized by TCR␣-specific antibodies.…”
Section: Fig 6 Characterization Of the Rw2-8c8 Antibody A Purifiedsupporting
confidence: 81%
See 4 more Smart Citations
“…5 and 7, respectively), which were regulated by activation and differentiation for certain epitopes, likely due to lipid raft-dependent arrangements or glycosylation. These results confirm our previous biosynthetic and phenotypic studies in CD3␥-deficient T cells (6) and extend the observations to primary T lymphocytes from normal individuals. Biosynthetic studies showed that CD8 ϩ but not CD4 ϩ CD3␥-deficient T cells contained a small ␣␤ heterodimer composed of abnormally glycosylated TCR␤ and an abnormally small CD3-associated chain that was not recognized by TCR␣-specific antibodies.…”
Section: Fig 6 Characterization Of the Rw2-8c8 Antibody A Purifiedsupporting
confidence: 81%
“…However, as shown above and in Ref. 6, the analysis of ␥ Ϫ TCR⅐CD3 complexes suggested the existence of hitherto unrecognized structural differences between both cell lineages. These results prompted us to search for qualitative ␣␤ TCR⅐CD3 complex differences in normal CD4 ϩ and CD8 ϩ primary T lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations